2013
DOI: 10.1016/j.cropro.2012.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate and fungicide effects on Cercospora leaf spot in four glyphosate-resistant sugar beet (Beta vulgaris) varieties

Abstract: a b s t r a c tThe potential for improved management of Cercospora leaf spot (CLS), caused by Cercospora beticola, using the herbicide glyphosate in glyphosate-resistant sugar beet varieties was investigated. Controlled field experiments were conducted in 2008 and 2009 to determine if glyphosate and glyphosateefungicide combinations improved the management of CLS in four commercial varieties of glyphosate-resistant sugar beet. Variety and fungicide main effects were significant for CLS development. However, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Glyphosate also failed to protect glyphosate resistant sugarbeet against infection by Cercospora beticola . A 2‐year field trial in North Dakota demonstrated that glyphosate applications resulted in the same disease ratings as non‐treated control .…”
Section: Glyphosate As a Fungicidementioning
confidence: 99%
See 1 more Smart Citation
“…Glyphosate also failed to protect glyphosate resistant sugarbeet against infection by Cercospora beticola . A 2‐year field trial in North Dakota demonstrated that glyphosate applications resulted in the same disease ratings as non‐treated control .…”
Section: Glyphosate As a Fungicidementioning
confidence: 99%
“…A standard fungicide, however, provided good protection. A similar trial in Michigan using four glyphosate resistant sugarbeet varieties also demonstrated that glyphosate had no effect on the management of Cercospora . Thus, although glyphosate did not reduce disease it also had no negative effects.…”
Section: Glyphosate As a Fungicidementioning
confidence: 99%